Interpretation Of Verses About Corruption - Faramita, Sela; Astri, Suci; Hati Nasution, Pelita; Hermanto, Edi (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Islam views the problem of corruption as a violation of religious and moral principles, as well as the importance of maintaining trust, justice, and integrity in every aspect. In the Qur'an, verses that discuss the problem of corruption are not found specifically. Likewise, in Arabic, there is no specific translation related to the word corruption. The word corruption in Arabic is usually translated as al-ikhtilas, al-rasywah, and al-fasad. Possible legal sanctions for perpetrators of corruption can be sentenced to hadd.